Factors Affecting the Immunity to Respiratory Syncytial Virus: From Epigenetics to Microbiome - Fonseca, Wendy; Lukacs, Nicholas W.; Ptaschinski, Catherine (Frontiers in Immunology, 2018)
Respiratory syncytial virus (RSV) is a common pathogen that infects virtually all children by two years of age and is the leading cause of hospitalization of infants worldwide. While most children experience mild symptoms, some children progress to severe lower respiratory tract infection. Those children with severe disease have a much higher risk of developing childhood wheezing later in life. Many risk factors are known to result in exacerbated disease, including premature birth and early age of RSV infection, when the immune system is relatively immature. The development of the immune system before and after birth may be altered by several extrinsic and intrinsic factors that could lead to severe disease predisposition in children who do not exhibit any currently known risk factors. Recently, the role of the microbiome and the resulting metabolite profile has been an area of intense study in the development of lung disease, including viral infection and asthma. This review explores both known risk factors that can lead to severe RSV induced disease as well as emerging topics in the development of immunity to RSV and the long-term consequences of severe infection.